Selection of a DNA aptamer against norovirus capsid protein VP1. Issue 2 (13th January 2014) - Beier, Rico; Pahlke, Claudia; Quenzel, Philipp; Henseleit, Anja; Boschke, Elke; Cuniberti, Gianaurelio; Labudde, Dirk
Abstract The genetically and antigenically diverse group of noroviruses is the major cause of human viral epidemic gastroenteritis worldwide. Virus detection and control are thus crucial topics when aiming at containing and preventing the resulting large and often persisting outbreaks. Aptamers provide a promising alternative to antibodies concerning their ability to bind and thus detect and influence bio‐active molecules. These small, single‐stranded oligonucleotides are able to bind to a multitude of possible target molecules with high affinity. For a specific target the highest affinity aptamers are found by screening a randomized library. In this work a DNA aptamer capable of binding to the norovirus genotype II.4 capsid protein VP1 was found. The general approach is thereby not limited to norovirus capsid, but could be extended to almost any kind of biologically relevant molecule. The development of the library enrichment was further computationally analyzed in order to describe the enrichment during screening. This is the basis for a later extensive characterization of both target and aptamers that could lead to insights regarding the functional coherence of both partners. An abstract model describing this coherence could be utilized to generate a target‐specific library, from which future aptamer screening runs could benefit.